PENERAPAN TEKNOLOGI PEMANENAN AIR HUJAN SKALA RUMAH TANGGA UNTUK PEMENUHAN KEBUTUHAN AIR BERSIH PADA DAERAH RAWA - Lubis, Sautma Forman Pangihutan; Haris, Virgo Trisep; Soehardi, Fitridawati (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
Clean water is often a major obstacle, the Rempak Village Community, Siak Districtuses water from rivers and shallow wells in their daily lives. However, the waterquality is not suitable for consumption as clean water for household scale. Theamount of rainwater for clean water needs on 2 types of gable and pyramid roofs.The method used is the Rational Model to find the amount of rainwater dischargethrough rainwater catchment. The rainfall data used for the study came from theHydrology Section of BWS III Sumatra with the location of the Bunga Raya (Siak)rainfall recording station from 2016 to 2022. The results of the study prove that thecontribution of rainfall during 2 years of rain with a 110m2 gable roof obtained arainfall contribution of 0.935m3 and dimensions of 0,3 × 0,135 × 0,5m, the use of a90m2 pyramid roof with a rainfall contribution of 0,765m3, the dimensions of thereservoir tank are 0,2 × 0,2 × 0,365m. The contribution of rainfall during the 5-year return period with a 110m2 gable roof is 1,122m3 with a reservoir tankdimension of 0,3 × 0,2 × 0,622m, while a 90m2 pyramid roof has a rainfallcontribution of 0.915m3 with a reservoir tank dimension of 0,2 × 0,1 × 0,635m. Theconclusion of the study is that the more different the roof type and roof area, theamount of rainwater for clean water needs is also different.